Canadian Social Work Field Education During a Global Pandemic: A Comparison of Student and Field Instructor Perspectives - Ossais, Jessica; Drolet, Julie; Alemi , Mohammad Idris; Collins, Tara; Au, Cara; Bogo, Marion; Charles, Grant; Franco, Monica; Henton, Jesse; Huang, Lavender Xin; et al. (Journal of Comparative Social Work, 2021)
The COVID-19 pandemic has significantly affected all aspects of social work education, including field education. The Transforming the Field Education Landscape (TFEL) partnership conducted two national online surveys to determine the impacts of the pandemic on social work field education. The first survey explored the perspectives of students and received responses from 367 Bachelor of Social Work (BSW) and Master of Social Work (MSW) students. The second survey was designed to gather the perspectives of field instructors, with 73 field instructors completing the survey. The article examines the impacts of the pandemic on social work practice, field supervision, practicum flexibility and accommodations in placement, the shift to remote learning, perceptions of future career prospects and the effects on wellness and mental health. This article contributes to an increased understanding of the strengths and challenges facing social work field education, and informs field planning and responses in a pandemic. The findings will be of interest to social work field education programmes, field education coordinators and directors, field instructors, field agencies and undergraduate and graduate social work students. Recommendations for social work field education are offered.